Men’s Help-Seeking for Distress: Navigating Varied Pathways and Practices - Vickery, Alex (Frontiers in Sociology, 2021)
There is a widely accepted dominant narrative surrounding men’s mental health help-seeking, that men are less likely to pursue formal mental health support on account of hegemonic masculine ideals that limit emotional expression and vulnerability. Across the literature, little attention has been given to the varied ways in which men can and will seek out help when experiencing mental health troubles. This paper reports findings from a qualitative study of men’s experiences of distress, specifically focused on their help-seeking and everyday coping and management of distress. Between 2016 and 2017, 38 individual interviews were carried out in South Wales, United Kingdom, with men of a range of ages (21–74 years of age) and social backgrounds. Analysis identifies nuanced help-seeking practices and pathways, emphasizing ways in which men can and will engage with mental health support. Some men struggled with articulating personal issues in mental health terms, and some portrayed ambivalence to help-seeking, yet at the same time reconstructed help-seeking to positively align with masculine values. The paper further highlights the significant influence of familial and friendship networks in the help-seeking process as well as the value of therapy for men experiencing mental health difficulties, challenging the idea that masculinity inhibits the disclosure of emotional problems. Awareness of the diversity of ways in which men can actively engage with their mental health is needed so that mental health support interventions and practitioners can best reach out to men experiencing distress and provide gender-sensitive support suitable to a range of different men.